The Implementation of Inclusive Learning In Muhammadiyah Elementary School of Dadapan, Yogyakarta - Saniya, Utma Masniyati; Widodo, Hendro; Suyatno; Santosa, Achadi Budi (American Journal of Education and Learning, 2020)
This research aims to illustrate an inclusive learning plan, implementation, and evaluation in Muhammadiyah elementary school of Dadapan, Turi, Yogyakarta. This research used a qualitative research type with a cases study approach. The data collection technique used in-depth interviews, observing the participants, and documentation. The data analysis technique used was data collection, data reduction, data presentation, and conclusion withdrawal. The research results show that: 1) inclusive learning plan was conducted by making learning devices based on curriculum 2013. Syllabus and learning implementation plan enforced generally, for children with special needs used the indicators according to their abilities. 2) The learning implementation used varied methods. The method frequently used was a lecture, discussion, question, and answer methods. The teachers used the methods according to the subject material and the student’s ability. Learning media used in the learning was media based-technology such as LCD and laptop. Learning media is a simple concrete tool used to serve the children with special needs who require assistance except using methods by the laptop. 3) The learning evaluation was based on curriculum 2013 by using four criteria of assessment, such as the assessment of social, spiritual, knowledge, and skills. The evaluation was conducted through two types of tests, including oral test and written test. The evaluation used an even and odd semester test conducted in the middle and the end of years. The findings of this study recommend the importance of planning, implementing, and evaluating inclusive learning for children with special needs in primary schools.